Assessing Suicidal Ideation and Behaviors Among Survivors of Childhood Brain Tumors and Their Mothers During Sociobehavioral Research. - Lucas, Matthew S; Brawner, Bridgette M; Hardie, Thomas L; Beacham, Barbara; Paidipati, Cynthia; Diaz, Magdaline; Lauer, Amy; Hobbie, Wendy L; Deatrick, Janet A (Oncology nursing forum, 2015)
To describe the development and feasibility of a protocol for nonpsychiatric subspecialty research staff members to screen research participants who endorse suicidal ideations or behaviors during data collection. .